Investigasi Bawah Permukaan Pada Area Kawah Sikidang, Dieng, Jawa Tengah Menggunakan Metode Geolistrik - Wiyuda, Muhammad Aji; Samodra, Saptono Budi; Utami, Pri (Universitas Negeri Gorontalo, 2022)
Sikidang crater geothermal manifestation area is located in Dieng geothermal field, Banjarnegara, Central Java Province, Indonesia. In 2019 more than 400,000 people visited Sikidang Crater tourism area. Some of the surface manifestation in this area include fumaroles, mud pools, steaming grounds, and altered ground. This research aim is to identify hydrothermal fluid below the surface and estimate the area of conductive zone using resistivity model from geoelectric data (dipole-dipole and Schlumberger configuration), surface temperature measurements, dan geological observation.Based on the results of 1D and 2D resistivity model, the low resistivity anomaly is thought to be a hydrothermal fluid that associated with surface geothermal manifestations appearence. The low resistivity anomaly also assumed to be associated with altered rocks in the study area, while the high resistivity anomaly is thought to be Pangonan andesitic lava with resistivity value above 1500 Î©.m. Several conductive zone dominantly identified in the Kawah Sikidang tourism area, however conductive zone also identified outside the tourism area.